The Influence of Integrated Digital Marketing, Supply Chain Management, and Business Performance on the Sustainability of MSMEs - Bayu Setyo Nugroho; Sri Marhaeni Salsiyah; Eva Purnamasari; Adam Afandi; Revalina Ayu Ramadhani (International Journal of Economics, Business and Innovation Research, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the supports for economic resilience which have an important role in the sustainable economic growth of society as a whole. In the midst of globalization and high competition, MSMEs must be able to face the challenges of globalization and the impact of the Covid-19 pandemic. Flexibility and adaptability play an important role in the sustainability of a business in responding to technological developments, changes in people's habits and increased competition. The Ministry of Industry continues to encourage the small and medium industrial sector to utilize digital technology and transform to improve business performance. The use of digital technology is very important as a form of adaptation for MSME players in improving business performance in the commitment to business continuity after the Covid-19 pandemic. Flexibility in implementing technological updates is also an important factor in the sustainability of a business in dealing with current and future challenges. Implementation is not that easy, so MSMEs need to apply a business reengineering model to apply digital technology as one of the strategies in implementing supply chain management in relation to establishing a Sustainability model. This research used a sample of 100 respondents with positions as owners or managers of MSMEs who have adapted to digital technology. This research uses Structural Equation Modeling (SEM) analysis through the Partial Least Square (PLS) program. This research provides a positive contribution to MSME actors in the form of models, methods and suggestions for managerial implications.